Current Techniques in Preoperative Imaging for Abdomen-based Perforator Flap Microsurgical Breast Reconstruction - Mathes, David W; Neligan, Peter C (Journal of Reconstructive Microsurgery, 2010)
Perforator-based microsurgical reconstruction of the breast has steadily increased since the introduction of the technique in the 1990s. The procedure appears to offer less postoperative pain, lower abdominal morbidity, and better preservation of the rectus muscles than the more conventional flaps. However, the major disadvantage of these flaps that they can be difficult to harvest, resulting in a longer operative times. The challenges in flap dissection are a result of the variability in the vascular anatomy of the deep inferior epigastric artery (DIEA) and its perforating branches through the rectus muscle. The location, number, and caliber of the perforators and the intramuscular trajectory of the DIEA branches vary greatly not only from individual to individual, but from one hemiabdomen to the other. The establishment of a presurgical map of the vessels on the abdomen facilitates surgical planning and may decrease operating room time, reduce intraoperative complications, and possibly improve outcomes. This article reviews the available techniques for preoperative planning with the currently available imaging modalities of handheld Doppler, color Doppler (duplex) ultrasound, computed tomography angiography, and magnetic resonance angiography.
Keywords: Perforator flap; breast reconstruction; CT angiography